Supported catalyst, preparation method thereof and method for synthesizing nitrile compound from low-carbon olefin
Through the supported catalyst Mo11.0BibLacCedMgeNifDgEhOx without iron, the problems of structural changes and Fe3+ overreduction during application are solved, the activity and stability of the catalyst are improved, and low-carbon olefins are achieved Efficient production of ammonia oxidation reaction.
Patent Information
- Application Number
- CN202310778030.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
During the application process, the existing Mo-Bi-Fe catalysts have structural changes and the over-reduction of Fe3+, which leads to a decrease in the performance of the catalyst with the extension of the running time, low activity and poor stability.
The supported catalyst without iron elements is used, the general formula is Mo11.0BibLacCedMgeNifDgEhOx, the carrier is silica, and the active component does not contain iron. Mo-Bi-La-Ce-Mg-Ni is used as the main active element. Improve the activity and stability of the catalyst through specific preparation methods.
The prepared catalyst has high activity and stability, and is suitable for industrial production of nitrile compounds produced by ammonia oxidation of low-carbon olefins. The low-carbon olefin conversion rate of the catalyst reaches more than 85% for more than 72 hours and is in situ at 20 times. The propylene conversion rate drop was less than 4.5 percentage points in the pulse test, showing good stability.
Smart Images

Figure CN119215917A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a supported catalyst and a preparation method thereof, and a method for synthesizing nitrile compounds from low-carbon olefins, belonging to the technical field of catalyst preparation. Background Art
[0002] At present, the industrial production of propylene ammoxidation to prepare unsaturated nitrile generally adopts fluidized bed ammoxidation process. As one of the core technologies of this process, the research and improvement of catalysts have always been valued. There are two main types of catalysts for industrial propylene ammoxidation to acrylonitrile: Mo-Bi series and Sb-Fe series. Among them, Mo-Bi series catalysts dominate, accounting for 95% of the propylene ammoxidation market, and Mo-Bi-Fe series is the main one.
[0003] By introducing metal components with variable valence states such as Fe, Ce and other elements into the catalyst, the redox performance of the catalyst is improved, and the effective state of the active components of the catalyst is restored faster. By introducing metal elements with ion radius greater than 0.8nm and less than 0.8nm, such as Cr, Ni, Mg, Mn, Zn, Al and other elements, they play the role of structural and electronic additives, and improve the structure and stability of the catalyst. By introducing rare earth elements, the amount of lattice oxygen in the catalyst is increased, and the catalytic performance of the catalyst is improved. By introducing elements such as Cs, Rb, P, B, Al, etc., the surface of the catalyst is modified and the acidity and alkalinity are adjusted to improve the selectivity and activity of the catalyst.
[0004] US 8455388 reported a Mo containing Ce element 12 Bi a Fe b A c D d E e F f G g Ce h O xCompound, wherein A is at least one of sodium, potassium, rubidium and cesium; D is at least one of nickel, cobalt, magnesium, zinc, manganese, calcium, strontium, cadmium and barium; E is at least one of chromium, tungsten, boron, aluminum, gallium, indium, phosphorus, arsenic, antimony, vanadium and tellurium; F is at least one of titanium, zirconium, hafnium, niobium, tantalum, thallium and germanium; G is at least one of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum and mercury. The ratio of each atom is limited to 0.05≤a≤7, 0.1≤b≤7, 0.01≤c≤5, 0.1≤d≤12, 0≤e≤5, 0≤f≤5, 0≤g≤0.2, 0.01≤h≤5, wherein 0.15≤(a+h) / d≤1, 0.8≤h / b≤5. The diffraction peak intensity of 2θ=28±0.3° in the XRD spectrum is selected as X, and the diffraction peak intensity of 2θ=26.5±0.3° is selected as Y, and the X / Y ratio is equal to or greater than 0.7. When 0.2≤(a+h) / d≤0.6, 1≤h / b≤3, the X / Y ratio is equal to or greater than 0.8, and when 0.3≤(a+h) / d≤0.5, 1.5≤h / b≤2, the X / Y ratio is equal to or greater than 0.9. It is believed that the addition of the carrier is insignificant in the catalyst preparation process, and the carrier can be introduced in any step before the slurry is dried.
[0005] However, the above Mo-Bi-Fe catalysts have structural changes and Fe 3+ Due to problems such as over-reduction, the catalyst performance tends to decline with the extension of operation time. (Petroleum Refining and Chemical Engineering, 2010, 41(11)27-31.) Summary of the invention
[0006] The invention relates to a method for preparing a nitrile compound synthesized from light olefins and a catalyst thereof, and mainly solves the problems of low activity and poor stability of existing catalysts for light olefin ammoxidation reaction.
[0007] One aspect of the present invention provides a supported catalyst, comprising a carrier and an active component represented by general formula I; the carrier comprises silicon dioxide; the active component does not contain iron;
[0008] Mo 11.0 Bi b La c Ce d Mg e Ni f D g E h O x Formula I;
[0009] In Formula I,
[0010] D is selected from at least one of Li, Na, K, Rb and Cs;
[0011] E is at least one selected from the group consisting of Ca, Pr, Nd, Sm, Zr, V, Nb, Cr, W, Co, Sb and Te;
[0012] The value range of b is 0.1~5.0; the value range of c is 0.1~5.0; the value range of d is 0.1~5.0; the value range of e is 0.1~5.0; the value range of f is 0.1~6.0; the value range of g is 0.1~5.0; the value range of h is 0.1~5.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the active component.
[0013] Optionally, the carrier accounts for 30% to 65% of the total weight of the catalyst.
[0014] Optionally, the optimal value range of b is 0.2~3.5; the optimal value range of c is 0.2~4.0; the optimal value range of d is 0.1~2.0; the optimal value range of e is 0.1~2.8; the optimal value range of f is 0.2~5.0; the optimal value range of g is 0.1~3.0; and the optimal value range of h is 0.1~2.0.
[0015] Another aspect of the present invention provides a method for preparing any of the above catalysts, comprising the steps of:
[0016] (a) obtaining a solution I containing Mo ions;
[0017] A solution II containing La ions is obtained;
[0018] Obtaining a solution III containing Bi ions, Ce ions, Mg ions, Ni ions, D ions, and E ions;
[0019] (b) adjusting the pH value of solution II to 3.5-7.0; preferably, adjusting the pH value of solution II to 4.0-6.5.
[0020] (c) the carrier precursor is mixed with solution I, solution II, and solution III to undergo a coprecipitation reaction to obtain a slurry;
[0021] (e) calcining the slurry in an atmosphere containing oxygen to obtain the catalyst; preferably, the volume content of oxygen in the atmosphere is 10% to 30%.
[0022] Optionally, the Mo ion-containing solution I is obtained by mixing a Mo source compound with a solvent I.
[0023] Optionally, the La ion-containing solution II is obtained by mixing a La source compound with a solvent II.
[0024] Optionally, the solution II containing Bi ions is obtained by mixing a Bi source compound with a solvent II.
[0025] Optionally, the solution II containing Ce ions is obtained by mixing a Ce source compound with a solvent II.
[0026] Optionally, the solution II containing Mg ions is obtained by mixing a Mg source compound with a solvent II.
[0027] Optionally, the solution II containing Ni ions is obtained by mixing a Ni source compound with a solvent II.
[0028] Optionally, the solution III containing D ions and E ions is obtained by mixing a D source compound and an E source compound with a solvent III.
[0029] Optionally, the Mo source compound is selected from a Mo-containing salt; the Mo-containing salt is preferably ammonium molybdate, more preferably at least one of ammonium heptamolybdate and ammonium tetramolybdate.
[0030] Optionally, the La source compound is selected from La nitrates.
[0031] Optionally, the Bi source compound is selected from Bi nitrates.
[0032] Optionally, the Ce source compound is selected from Ce nitrates.
[0033] Optionally, the Mg source compound is selected from Mg nitrates.
[0034] Optionally, the Ni source compound is selected from Ni nitrates.
[0035] Optionally, the D source compound is selected from D nitrate.
[0036] Optionally, the E source compound is selected from E nitrates.
[0037] Optionally, the carrier precursor is selected from silica sol.
[0038] Optionally, the concentration of Mo ions in solution I is 0.5-5.0 mol / L.
[0039] Optionally, the concentration of La ions in solution II is 0.5 to 5.0 mol / L.
[0040] Optionally, the concentration of Bi ions in solution III is 0.1 to 3.0 mol / L;
[0041] Optionally, the concentration of Ce ions in solution III is 0.05 to 2.0 mol / L;
[0042] Optionally, the concentration of Mg ions in solution III is 0.5 to 2.5 mol / L;
[0043] Optionally, the concentration of Ni ions in solution III is 1.0 to 9.5 mol / L;
[0044] Optionally, the concentration of D ions in solution III is 0.01 to 2.0 mol / L;
[0045] Optionally, the concentration of E ions in solution III is 0.05 to 5.0 mol / L;
[0046] Optionally, the total concentration of Bi ions, Ce ions, Mg ions, Ni ions, and D and E ions in solution III is 2.0 to 18.0 mol / L.
[0047] Optionally, the slurry is dried in an oven at a temperature ranging from 110 to 180° C., preferably 110 to 130° C., and the drying time is 12 to 48 hours, preferably 24 to 36 hours.
[0048] Optionally, after drying, the slurry is tableted, crushed and sieved, and the particle size ranges from 40 to 100 meshes, preferably 60 to 80 meshes.
[0049] Optionally, the slurry is calcined in an atmosphere containing oxygen to obtain the catalyst; preferably, the volume content of oxygen in the atmosphere is 10% to 30%.
[0050] Optionally, the calcination conditions include: a temperature of 500-680° C. and a time of 0.2-4.0 hours. Preferably, the calcination conditions include: a temperature of 550-650° C. and a time of 0.5-2.5 hours.
[0051] Optionally, adjusting the pH value of the solution II with at least one inorganic base can improve the activity and stability of the catalyst.
[0052] Optionally, the rate of adding the inorganic base to the solution II is 0.2 to 5.0 ml / min, preferably 0.5 to 2.0 ml / min.
[0053] Optionally, the inorganic base is preferably ammonium hydroxide, and its volume concentration range is 5% to 20%, preferably 5% to 15%.
[0054] In another aspect, the present invention provides a method for producing nitrile compounds from light olefins, comprising raw materials of light olefins, ammonia and oxygen-containing gas, contacting with a catalyst, undergoing an ammoxidation reaction, and producing nitrile compounds; the catalyst is any one of the above-mentioned supported catalysts, or a supported catalyst obtained by any of the above-mentioned preparation methods.
[0055] Optionally, the low-carbon olefin is a C2-C4 olefin; preferably propylene.
[0056] Optionally, the nitrile compound is an unsaturated nitrile; preferably acrylonitrile.
[0057] Optionally, the reaction conditions include: a molar ratio of low-carbon olefins, ammonia, and air of 1:(1.05-1.3):(9.2-9.8); a reaction temperature of 420-440°C, a reaction pressure of 0.06-0.14 MPa; a propylene load (WWH) of the catalyst of 0.06-0.12 h -1 .
[0058] Optionally, the conversion rate of the light olefins is greater than 85% after the reaction is carried out for 72 hours; preferably, it is 85.0% to 89.8%.
[0059] Optionally, an in-situ pulse method is used to test the reaction performance of lattice oxygen in the catalyst, and the decrease in the conversion rate of light olefins within the range of 20 tests is less than 4.5 percentage points.
[0060] The supported catalyst prepared by the invention does not contain iron element, takes Mo-Bi-La-Ce-Mg-Ni as the main active element, has good activity and stability, and can be used in the industrial production of nitrile compounds by ammoxidation of low-carbon olefins.
[0061] Instruction Manual
[0062] Figure 1 The test results of propylene conversion of catalyst A, catalyst B, catalyst F and catalyst J prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 5 after 20 in-situ pulses are shown, and their stability is shown according to the decreasing trend of the conversion rate. DETAILED DESCRIPTION
[0063] As one embodiment, the catalyst for synthesizing nitrile compounds from low-carbon olefins used in the present invention comprises a carrier and an active component represented by the following general formula: Mo 11.0 Bi b La c Ce d Mg e Ni f D g E h O x , wherein D is selected from at least one of Li, Na, K, Rb and Cs; and E is selected from at least one of Ca, Pr, Nd, Sm, Zr, V, Nb, Cr, W, Co, Sb and Te.
[0064] The catalyst was prepared by the following steps:
[0065] (1) dissolving a salt containing Mo ions in a solvent I to obtain a solution I; the salt containing Mo ions is preferably ammonium molybdate; and the solvent I is preferably water;
[0066] (2) dissolving a La-containing salt in a solvent II to obtain a solution II, and adjusting the pH value thereof with at least one inorganic base; the La-containing salt is preferably lanthanum nitrate; and the solvent II is preferably water;
[0067] (3) dissolving at least one of a salt containing Bi ions, Ce ions, Mg ions, Ni ions, and a salt containing D ions and a salt containing E ions in a solvent III to obtain a solution III; the salt containing Bi ions is preferably bismuth nitrate; the salt containing Ce ions is preferably cerium nitrate; the salt containing Mg ions is preferably magnesium nitrate; the salt containing Ni ions is preferably nickel nitrate; the salt containing D ions is preferably nitrate; the salt containing E ions is preferably nitrate;
[0068] (4) After mixing a required amount of silica sol with solution I, solution II and solution III are added in sequence to immediately obtain a coprecipitation slurry;
[0069] (5) The slurry is dried in an oven at a temperature ranging from 110 to 180° C. for 12 to 48 hours before calcination; after drying, it is pressed into tablets, crushed and sieved, and the particle size ranges from 40 to 100 meshes;
[0070] (6) The catalyst is calcined at 500-680°C in air atmosphere for 0.2-4.0 hours.
[0071] The present invention is further described below by means of specific examples, but the present invention is not limited by the following examples.
[0072] Example 1
[0073] 98.5 g (NH4)6Mo7O 24 ·4H2O was dissolved in 163 g of water to obtain solution (I), in which the concentration of Mo ions was 3.4 mol / L.
[0074] Heat and dissolve 13.9 g of La(NO3)3·6H2O in 65 g of water, with the concentration of La ions being 0.5 mol / L. Then, add a 10% dilute ammonia solution at a rate of 1 ml / min while stirring to adjust the pH value to 6.0 to obtain solution (II).
[0075] 13.2 g Bi(NO3)3·5H2O, 1.2 g Ca(NO3)2·4H2O, 21.4 g Mg(NO3)2·6H2O, 4.6 g Ce(NO3)3·6H2O, 65.8 g Ni(NO3)2·6H2O, 1.0 g CsNO3 and 0.55 g CrO3 were heated and dissolved in 180 g water to obtain solution (III). The solution (III) contained Bi ion concentration of 0.15 mol / L, Mg ion concentration of 0.5 mol / L, Ce ion concentration of 0.06 mol / L, Ni ion concentration of 1.3 mol / L, D ion concentration of 0.03 mol / L, E ion concentration of 0.06 mol / L, and the total ion concentration of metal elements contained in solution (III) was 2.1 mol / L.
[0076] 156 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 120°C for 24 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 600°C in a 10% O2 / He atmosphere for 2 hours to obtain catalyst A.
[0077] In catalyst A, after in-situ pulse testing:
[0078] The active component is Mo 11.0 Bi 0.5 La 0.6 Ce 0.2 Mg 1.6 Ni 4.5 Cs 0.1 Ca 0.1 Cr 0.1 O x , the content of carrier SiO2 is 35.1wt%.
[0079] Example 2
[0080] 77.9 g (NH4)6Mo7O 24 ·4H2O was dissolved in 142 g of water to obtain solution (I), in which the concentration of Mo ions was 3.1 mol / L.
[0081] 16.3 g of La(NO3)3·6H2O was heated and dissolved in 12 g of water, with the concentration of La ions being 3.1 mol / L. Then, a 5% dilute ammonia solution was added at a rate of 1.5 ml / min while stirring to adjust the pH value to 6.5 to obtain solution (II).
[0082] 11.5 grams of Bi(NO3)3·5H2O, 10.8 grams of Mg(NO3)2·6H2O, 3.2 grams of Ce(NO3)3·6H2O, 48.2 grams of Ni(NO3)2·6H2O, 1.3 grams of H6TeO6, 9.4 grams of Zr(NO3)4·5H2O, 5.4 grams of Nd(NO3)3·6H2O and 5.1 grams of RbNO3 were heated and dissolved in 19 grams of water to obtain solution (III). The solution (III) contained Bi ion concentration of 1.2 mol / L, Mg ion concentration of 2.2 mol / L, Ce ion concentration of 0.4 mol / L, Ni ion concentration of 8.7 mol / L, D ion concentration of 1.8 mol / L, E ion concentration of 2.1 mol / L, and the total metal element ion concentration contained in solution (III) was 16.5 mol / L.
[0083] 182 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 110°C for 36 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 620°C in an air atmosphere for 2 hours to obtain catalyst B.
[0084] In catalyst B, after in-situ pulse testing:
[0085] The active component is Mo 11.0 Bi 0.6 La 0.9 Ce 0.2 Mg 1.1 Ni 4.1 R 0.9 Te 0.1 Zr 0.5 Nd 0.3 O x , the content of carrier SiO2 is 42.3wt%.
[0086] Example 3
[0087] 89.8 g (NH4)6Mo7O 24 ·4H2O was dissolved in 152 g of water to obtain solution (I), in which the concentration of Mo ions was 3.3 mol / L.
[0088] Heat and dissolve 25.2 g of La(NO3)3·6H2O in 26 g of water, with the concentration of La ions being 2.2 mol / L. Then, add 8% dilute ammonia solution at a rate of 2.0 ml / min while stirring to adjust the pH value to 5.5 to obtain solution (II).
[0089] 12.2 grams of Bi(NO3)3·5H2O, 4.4 grams of Mg(NO3)2·6H2O, 7.2 grams of Ce(NO3)3·6H2O, 65.9 grams of Ni(NO3)2·6H2O, 7.7 grams of Zr(NO3)4·5H2O, 0.2 grams of KOH, 0.9 grams of CrO3 and 2.1 grams of RbNO3 were heated and dissolved in 35 grams of water to obtain solution (III). The solution (III) contained Bi ion concentration of 0.7 mol / L, Mg ion concentration of 0.5 mol / L, Ce ion concentration of 0.5 mol / L, Ni ion concentration of 6.5 mol / L, D ion concentration of 0.5 mol / L, E ion concentration of 0.5 mol / L, and total metal element ion concentration of solution (III) was 9.2 mol / L.
[0090] 176 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 130°C for 30 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 600°C in a 30% O2 / N2 atmosphere for 2.5 hours to obtain catalyst C.
[0091] In catalyst C, after in-situ pulse testing:
[0092] The active component is Mo 11.0 Bi 0.6 La 1.3 Ce 0.4 Mg 0.4 Ni 4.9 K 0.1 R 0.3 Zr 0.4 Cr 0.2 O x , the content of carrier SiO2 is 38.2wt%.
[0093] Example 4
[0094] 89.9 g (NH4)6Mo7O 24 ·4H2O was dissolved in 135 g of water to obtain solution (I), in which the concentration of Mo ions was 3.8 mol / L.
[0095] Heat and dissolve 38.5 g of La(NO3)3·6H2O in 18 g of water, with the concentration of La ions being 4.9 mol / L. Then, add a 15% dilute ammonia solution at a rate of 0.2 ml / min while stirring to adjust the pH value to 4.5 to obtain solution (II).
[0096] 31.2 g Bi(NO3)3·5H2O, 9.8 g Mg(NO3)2·6H2O, 6.5 g Ce(NO3)3·6H2O, 59.1 g Ni(NO3)2·6H2O, 3.9 g Ca(NO3)2·4H2O, 4.2 g Nd(NO3)3·6H2O, 1.1 g CsNO3 and 13.7 g (NH4) 10 H2(W2O7)6·XH2O was heated and dissolved in 25 g of water to obtain solution (III). The Bi ion concentration of solution (III) was 2.6 mol / L, the Mg ion concentration was 1.5 mol / L, the Ce ion concentration was 0.6 mol / L, the Ni ion concentration was 8.1 mol / L, the D ion concentration was 0.2 mol / L, the E ion concentration was 3.2 mol / L, and the total ion concentration of metal elements contained in solution (III) was 16.2 mol / L.
[0097] 196 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 120°C for 24 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 620°C in an air atmosphere for 1.5 hours to obtain catalyst D.
[0098] Catalyst D, after in-situ pulse testing:
[0099] The active component is Mo 11.0 Bi 1.4 La 1.9 Ce 0.3 Mg 0.8 Ni 4.4 Cs 0.1 Ca 0.4 Nd 0.2 W 1.2 O x , the content of carrier SiO2 is 36.3wt%.
[0100] Example 5
[0101] 90.3 g (NH4)6Mo7O 24 ·4H2O was dissolved in 102 g of water to obtain solution (I), in which the concentration of Mo ions was 5.0 mol / L.
[0102] 33.0 g of La(NO3)3·6H2O was heated and dissolved in 26 g of water, with the concentration of La ions being 2.9 mol / L. Then, a 10% dilute ammonia solution was added at a rate of 0.5 ml / min while stirring to adjust the pH value to 6.0 to obtain solution (II).
[0103] 29.5 g Bi(NO3)3·5H2O, 15.1 g Mg(NO3)2·6H2O, 6.7 g Ce(NO3)3·6H2O, 43.6 g Ni(NO3)2·6H2O, 3.2 g H6TeO6, 0.5 g CrO3, 5.8 g RbNO3 and 13.7 g (NH4) 10 H2(W2O7)6·XH2O was heated and dissolved in 28 g of water to obtain solution (III). The Bi ion concentration of solution (III) was 2.2 mol / L, the Mg ion concentration was 2.1 mol / L, the Ce ion concentration was 0.6 mol / L, the Ni ion concentration was 5.4 mol / L, the D ion concentration was 1.4 mol / L, the E ion concentration was 2.6 mol / L, and the total ion concentration of metal elements contained in solution (III) was 14.3 mol / L.
[0104] 188 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 110°C for 36 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 610°C in a 15% O2 / He atmosphere for 2.0 hours to obtain catalyst E.
[0105] In catalyst E, after in-situ pulse testing:
[0106] The active component is Mo 11.0 Bi 1.3 La 1.6 Ce 0.3 Mg 1.3 Ni 3.2 R 0.8 Te 0.3 Cr 0.1 W 1.2 O x , the content of carrier SiO2 is 35.7wt%.
[0107] Comparative Example 1
[0108] The catalyst F was prepared according to the method of Example 1, except that the solution (II) was not added, and finally the catalyst F was obtained.
[0109] In catalyst F, the active component is Mo 11.0 Bi 0.5 Ce 0.2 Mg 1.6 Ni 4.5 Cs 0.1 Ca 0.1 Cr 0.1 O x , the content of carrier SiO2 is 36.2wt%.
[0110] Comparative Example 2
[0111] Catalyst G was finally obtained by the method of Example 1, except that the inorganic base was not added to solution (II) at a constant flow rate of 1 ml / min, but was added to solution (II) all at once so that its pH value immediately reached 6.0.
[0112] In catalyst G, after in-situ pulse testing:
[0113] The active component is Mo 11.0 Bi 0.5 La 0.6 Ce 0.2 Mg 1.6 Ni 4.5 Cs 0.1 Ca 0.1 Cr 0.1 O x , the content of carrier SiO2 is 35.1%.
[0114] Comparative Example 3
[0115] The catalyst was prepared according to the method of Example 2, except that 17.7 g of Fe(NO3)3·9H2O was added to the solution (III) in addition to other metal elements, so that the total ion concentration of metal elements contained in the solution (III) was 13.0 mol / L. Catalyst H was obtained, and the active component was Mo after in-situ pulse test. 11.0 Bi 0.6 Fe 1.1 La 0.9 Ce 0.2 Mg 1.1 Ni 4.1 R 0.9 Te 0.1 Zr 0.5 Nd 0.3 O x , the content of carrier SiO2 is 41.4wt%.
[0116] Comparative Example 4
[0117] The catalyst was prepared according to the method of Example 2, except that the La element was replaced by Fe element in the same ratio, that is, 15.2 g of Fe(NO3)3·9H2O was added to 12 g of water and heated to dissolve. At this time, the concentration of Fe ions in solution (II) was 3.1 mol / L. Catalyst I was obtained. After in-situ pulse test, the active component was Mo 11.0 Bi 0.6 Fe 0.9 Ce 0.2 Mg 1.1 Ni 4.1 R 0.9 Te0.1 Zr 0.5 Nd 0.3 O x , the content of carrier SiO2 is 43.1wt%.
[0118] Comparative Example 5
[0119] The Mo-Bi-Fe catalyst with better catalytic performance was prepared according to the following method.
[0120] 99.8 g (NH4)6Mo7O 24 ·4H2O was dissolved in 180 g of water to obtain solution (I), in which the concentration of Mo ions was 3.1 mol / L.
[0121] 34.8 g of Fe(NO3)3·9H2O was heated and dissolved in 21 g of water, and the concentration of Fe ions was 4.1 mol / L to obtain solution (II).
[0122] 11.5 grams of Bi(NO3)3·5H2O, 10.9 grams of Mg(NO3)2·6H2O, 8.2 grams of Zr(NO3)4·5H2O, 12.2 grams of Nd(NO3)3·6H2O, 21.3 grams of Pr(NO3)3·6H2O, 3.2 grams of CrO3, 6.8 grams of RbNO3 and 54.2 grams of Ni(NO3)2·6H2O were heated and dissolved in 28 grams of water to obtain solution (III). The solution (III) contained Bi ion concentration of 0.8 mol / L, Mg ion concentration of 1.5 mol / L, Ni ion concentration of 6.7 mol / L, D ion concentration of 1.6 mol / L, E ion concentration of 4.6 mol / L, and the total metal element ion concentration contained in solution (III) was 15.2 mol / L.
[0123] 168 g of silica sol with a silicon content of 40% was weighed and mixed with solution (I), and then solution (II) and solution (III) were added in sequence to immediately obtain a coprecipitation slurry. The slurry was dried in an oven at a temperature of 120°C for 24 hours, then tableted and crushed and sieved, and 60-80 mesh particles were taken and calcined in a muffle furnace at 620°C in an air atmosphere for 2.0 hours to obtain catalyst J.
[0124] Catalyst J, after in-situ pulse testing:
[0125] The active component is Mo 11.0 Bi 0.5 Fe 1.7 Mg 0.8 Ni 3.6 R 0.9 Zr 0.4 Nd 0.5 Pr 1.0 Cr 0.6 Ox , the content of carrier SiO2 is 33.7wt%.
[0126] Test Case
[0127] Activity test
[0128] The catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were used to perform ammoxidation of propylene to produce acrylonitrile under the following reaction conditions. The catalyst composition is shown in Table 1, and the catalyst activity and stability test results are shown in Table 2.
[0129] Reactor: Φ6 mm fixed bed reactor; catalyst loading: 1.5 g.
[0130] Reaction conditions: temperature 430°C; pressure normal pressure; raw material ratio (molar): propylene / ammonia / air = 1 / 1.25 / 9.7;
[0131] Catalyst propylene load (WWH) 0.10 hours -1 .
[0132] Calculation method of propylene conversion (mol%) and acrylonitrile recovery:
[0133]
[0134]
[0135] Characterization test of the ability of lattice oxygen to participate in the reaction of catalysts
[0136] For the two reactions of oxidation of light olefins and ammoxidation, based on the reaction mechanism, the light olefins are dehydrogenated and activated at the same active center on the catalyst. In essence, the light olefins undergo a redox reaction with the lattice oxygen in the catalyst. Therefore, the ability of the lattice oxygen in the catalyst to participate in the reaction directly affects the activity and stability of the catalyst.
[0137] By using the in-situ light olefin pulse method, since the lattice oxygen in the catalyst directly reacts with the light olefin, the ability of the lattice oxygen to participate in the reaction can be directly observed.
[0138] The specific test method is as follows:
[0139] The in-situ pulse test was carried out on a chemical adsorption device equipped with a gas chromatograph, with a catalyst sample loading of 0.3 g, a pulse gas quantitative loop of 0.25 ml, and a pulse interval of 11 min. An inert gas was used as a carrier gas, preferably nitrogen, argon and helium, and most preferably helium. The tail gas was detected for composition changes using a hydrogen flame ionization detector FID and a thermal conductivity TCD detector.
[0140] Before testing the catalyst sample, an inert gas was purged for 2 hours at a reaction temperature of 430°C to remove the substances adsorbed on the surface, and then 20 pulses were performed to calculate the conversion rate of propylene in each pulse. By analyzing the conversion rate of propylene each time, it can be found that the conversion rate of propylene is directly proportional to the ability of lattice oxygen to participate in the reaction, and the reduction in conversion rate is proportional to the stability of the catalyst, that is, the greater the reduction, the worse the stability of the catalyst.
[0141] Calculation method of propylene conversion (mol%):
[0142]
[0143] The percentage reduction of propylene conversion after 20 in-situ pulses is calculated as follows:
[0144] Propylene conversion rate reduction percentage after 20 in-situ pulses = 1st propylene conversion rate - 20th propylene conversion rate
[0145] Test results see Figure 1 It can be seen that after 20 propylene in-situ pulses, the propylene conversion rate of catalyst A prepared in Example 1 decreased by only 4.5 percentage points, indicating that the catalyst has high stability. After 20 propylene in-situ pulses, the propylene conversion rate of catalyst B prepared in Example 2 also decreased slightly, at 6.7 percentage points.
[0146] Compared with Examples 1 and 2, the propylene conversion rate of Catalyst F prepared in Comparative Example 1 decreased significantly by 36.9 percentage points after 20 propylene in-situ pulses; the propylene conversion rate of Catalyst J prepared in Comparative Example 5 decreased significantly by 29.9 percentage points after 20 propylene in-situ pulses.
[0147] Table 1 Catalyst composition
[0148]
[0149]
[0150] Table 2 Catalyst composition and evaluation performance
[0151]
Claims
1. A supported catalyst comprising a carrier and an active component represented by general formula I; The carrier includes silicon dioxide; the active component does not contain iron; Mo 11.0 Bi b La c Ce d Mg e Ni f D g E h O x Formula I; In Formula I, D is selected from at least one of Li, Na, K, Rb and Cs; E is at least one selected from the group consisting of Ca, Pr, Nd, Sm, Zr, V, Nb, Cr, W, Co, Sb and Te; The value range of b is 0.1~5.0; the value range of c is 0.1~5.0; the value range of d is 0.1~5.0; the value range of e is 0.1~5.0; the value range of f is 0.1~6.0; the value range of g is 0.1~5.0; the value range of h is 0.1~5.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the active component.
2. The supported catalyst according to claim 1, characterized in that The carrier accounts for 30% to 65% of the total weight of the catalyst; And / or, the value range of b is 0.2-3.5; the value range of c is 0.2-4.0; the value range of d is 0.1-2.0; the value range of e is 0.1-2.8; the value range of f is 0.2-5.0; the optimal value range of g is 0.1-3.0; and the value range of h is 0.1-2.
0.
3. The method for preparing the supported catalyst according to claim 1 or 2, comprising the steps of: (a) obtaining a solution I containing Mo ions; A solution II containing La ions is obtained; Obtaining a solution III containing Bi ions, Ce ions, Mg ions, Ni ions, D ions, and E ions; (b) adjusting the pH value of solution II to 3.5 to 7.0; (c) the carrier precursor is mixed with solution I, solution II, and solution III to undergo a coprecipitation reaction to obtain a slurry; (e) calcining the slurry in an atmosphere containing oxygen to obtain the catalyst; preferably, the volume content of oxygen in the atmosphere is 10% to 30%.
4. The preparation method according to claim 3, characterized in that: The Mo ion-containing solution I is obtained by mixing a Mo source compound with a solvent I; And / or, the La ion-containing solution II is obtained by mixing a La source compound with a solvent II; And / or, the solution III containing Bi ions, Ce ions, Mg ions, Ni ions, D ions and E ions is obtained by mixing a Bi source compound, a Ce source compound, a Mg source compound, a Ni source compound, a D source compound and an E source compound with a solvent III; Preferably, the Mo source compound is selected from a salt containing Mo; the Mo-containing salt is preferably ammonium molybdate, more preferably at least one of ammonium heptamolybdate and ammonium tetramolybdate; And / or, the La source compound is selected from La nitrate; And / or, the Bi source compound is selected from Bi nitrate; And / or, the Ce source compound is selected from Ce nitrates; And / or, the Mg source compound is selected from Mg nitrate; And / or, the Ni source compound is selected from Ni nitrate; And / or, the D source compound is selected from the nitrate of D; And / or, the E source compound is selected from nitrates of E; and / or, the carrier precursor is selected from silica sol; and / or, the concentration of Mo ions in solution I is 0.5 to 5.0 mol / L; and / or, the concentration of La ions in solution II is 0.5 to 5.0 mol / L; and / or, the concentration of Bi ions in solution III is 0.1 to 3.0 mol / L; and / or, the concentration of Ce ions in solution III is 0.05 to 2.0 mol / L; and / or, the concentration of Mg ions in solution III is 0.5 to 2.5 mol / L; and / or, the concentration of Ni ions in solution III is 1.0 to 9.5 mol / L; and / or, the concentration of D ions in solution III is 0.01 to 2.0 mol / L; and / or, the concentration of E ions in solution III is 0.05 to 5.0 mol / L; And / or, the total concentration of Bi, Ce, Mg, Ni, and D, E ions in solution III is 2.0 to 18.0 mol / L.
5. The preparation method according to any one of claims 3 to 4, characterized in that: adjusting the pH value of the solution II with at least one inorganic base; Preferably, the rate at which the inorganic base is added to solution II is 0.2 to 5.0 ml / min, preferably 0.5 to 2.0 ml / min; and / or, adjusting the pH value of solution II to 4.0 to 6.5; And / or, the inorganic base is preferably ammonium hydroxide, and its volume concentration range is 5% to 20%, preferably 5% to 15%.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The method comprises the following steps: drying the slurry in an oven at a temperature range of 110 to 180° C., preferably 110 to 130° C., for 12 to 48 hours, preferably 24 to 36 hours, before calcination; and then crushing and sieving the slurry to a particle size range of 40 to 100 meshes, preferably 60 to 80 meshes.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The calcination conditions include: temperature 500-680°C, time 0.2-4.0 hours; Preferably, the calcination conditions include: temperature of 550-650° C. and time of 0.5-2.5 hours.
8. A method for producing nitrile compounds from low-carbon olefins, characterized in that: A raw material comprising low-carbon olefins, ammonia and an oxygen-containing gas is contacted with a catalyst to undergo an ammoxidation reaction to produce nitrile compounds; the catalyst is a supported catalyst as claimed in claim 1 or 2, or a supported catalyst obtained by the preparation method of any one of claims 3 to 7.
9. The method according to claim 8, characterized in that The oxygen-containing gas is air; and / or, the low carbon olefin is a C2-C4 olefin, preferably propylene; And / or, the nitrile compound is an unsaturated nitrile; preferably acrylonitrile; And / or, the ammoxidation reaction conditions include: the molar ratio of light olefins, ammonia, and air is 1:(1.05-1.3):(9.2-9.8); the reaction temperature is 420-440°C, the reaction pressure is 0.06-0.14 MPa; the propylene load (WWH) of the catalyst is 0.06-0.12 h -1 .
10. The method according to claim 8 or 9, characterized in that: The conversion rate of the light olefins is greater than 85% after the reaction is carried out for 72 hours; preferably 85.0% to 89.8%; And / or, the in-situ pulse method is used to test the ability of lattice oxygen in the catalyst to participate in the reaction, and the decrease in the conversion rate of light olefins within the range of 20 tests is less than 4.5 percentage points.
Citation Information
Cited By
Supported acrylonitrile catalyst and preparation method thereof
CN121042015A
A supported acrylonitrile catalyst and its preparation method
CN121042015B